The application of proteomic approaches to the study of mammalian spermatogenesis and sperm function. (2nd September 2013) - MacLeod, Graham; Varmuza, Susannah
Abstract : Spermatogenesis is the process by which terminally differentiated sperm are produced from male germline stem cells. This complex developmental process requires the coordination of both somatic and germ cells through phases of proliferation, meiosis, and morphological differentiation, to produce the cell responsible for the delivery of the paternal genome. With infertility affecting 15% of all couples, furthering our understanding of spermatogenesis and sperm function is vital for improving the diagnosis and treatment of male factor infertility. The emerging use of proteomic technologies has played an instrumental role in our understanding of spermatogenesis by providing information regarding the genes involved. This article reviews existing proteomic literature regarding spermatogenesis and sperm function, including the proteomic characterization of spermatogenic cell types, subcellular proteomics, post‐translational modifications, interactomes, and clinical studies. Future directions in the application of proteomics to the study of spermatogenesis and sperm function are also discussed. Abstract : Spermatogenesis is a complex developmental process involving numerous germ cell types, that to date cannot be fully modelled in culture. Proteomic approaches have played an instrumental role in our understanding of spermatogenesis and sperm function. This article reviews existing proteomic literature and available datasets regarding the proteomic characterization of spermatogenic cell types, subcellular proteomics, post‐translational modifications, interactomes and clinical studies.